Enhancing SMEs Competitiveness through ICT Adoption: A Case Study of Gunung Puntang Coffee - Nike Yosephine; Ahmad Sulaeman; Sapta Raharja (International Journal of Economics Accounting and Management, 2025)
This paper aims to examine the level, influencing factors, and effectiveness of Information and Communication Technology (ICT) adoption in enhancing the competitiveness of Gunung Puntang coffee SMEs. A quantitative research design was employed using survey data from coffee SMEs in Gunung Puntang. The analysis was conducted with SPSS regression to evaluate the influence of individual, organizational, technological, and external environmental factors on ICT adoption and competitiveness. The results indicate that ICT adoption significantly contributes to improving market access, operational efficiency, and brand visibility of coffee SMEs. However, adoption remains constrained by low digital literacy, limited financial resources, and inadequate infrastructure. The novelty of this study lies in formulating holistic and context-specific strategies to enhance ICT adoption in Gunung Puntang coffee SMEs. The study proposes strategic directions emphasizing the enhancement of ICT literacy through training, coupled with improved access to digital infrastructure, particularly stable internet connectivity. These strategies are expected to optimize ICT adoption among SMEs and strengthen their competitiveness in the growing West Java coffee market.